IMPLEMENTASIRIZOBAKTERI SEBAGAI PUPUK HAYATIUNTUK MENDUKUNG PERTANIAN BERKELANJUTAN DI KABUPATEN SOLOK - Milda Ernita; Diyanti, Afri Rona; Thesiwati, Aslan Sari; Ermawati, Ermawati; Sunadi, Sunadi; Haryoko, Widodo; Yulfidesi, Yulfidesi (Jurnal Hilirisasi IPTEKS, 2025)
Simpang Tanjung Nan Ampek Village, located in the Danau Kembar Subdistrict of Solok Regency, is one of the key potato-producing areas. Potato production in Solok Regency has reached 28,939 tonnes per hectare (BPS, 2023). To date, potato cultivation in this region has been heavily dependent on synthetic fertilisers and high levels of pesticide use, which can have detrimental effects on both biotic and abiotic components of the environment. One viable solution to mitigate these impacts is the application of local microorganisms, particularly Plant Growth-Promoting Rhizobacteria (PGPR), which are well-known for their ability to enhance nutrient availability, promote plant growth, and improve overall plant health. This community engagement programme aimed to increase farmers’ knowledge regarding the role of PGPR in enhancing potato growth and productivity. The activity was conducted in Simpang Tanjung Nan Ampek Village, Danau Kembar Subdistrict, Solok Regency, in February 2025. The programme employed three main methods: (1) socialisation activities to raise awareness of the functions and benefits of PGPR, (2) training sessions on PGPR propagation techniques, and (3) the practical application of PGPR on potato crops. The programme yielded positive outcomes. Farmers gained a better understanding of the benefits of PGPR, as well as the skills required for its propagation and application on potato plants. The educational and hands-on approaches used in the programme significantly improved the farmers’ knowledge and competence in implementing PGPR.